2019
DOI: 10.1088/1361-6463/ab1892
|View full text |Cite
|
Sign up to set email alerts
|

Tunable all-graphene-dielectric single-band terahertz wave absorber

Abstract: We propose an all-graphene-dielectric tunable terahertz absorber composed of a graphene microstructure layer, a dielectric spacer layer and a metallic ground plane. The absorption performance and internal mechanism of the absorber have been comprehensively analyzed. When E f changes from 0 eV to 0.6 eV, the absorption peak changes from 0.48 THz to 1.579 THz. In addition, we present a novel equivalent circuit model to analyze the mechanism of the absorber. The numerical calculation results are basically consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…However, these approaches suffer from technical difficulties due to larger size and thickness which limits practical applications. In addition, proposed absorber utilizing single metallic structure demonstrates seven absorption peaks with polarization insensitive characteristics which is better than previously reported MMA [10,12,14,30,32].…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…However, these approaches suffer from technical difficulties due to larger size and thickness which limits practical applications. In addition, proposed absorber utilizing single metallic structure demonstrates seven absorption peaks with polarization insensitive characteristics which is better than previously reported MMA [10,12,14,30,32].…”
Section: Resultsmentioning
confidence: 65%
“…The real (Z) and imaginary (Z) should be nearly one and zero, respectively, as impedance of the MMA must be equal to free space impedance to achieve perfect absorption [10,28]. [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the electromagnetic shielding effectiveness (EMI SE) could be written in dB as follow [16,34,35]: Because of the obvious SPPs in the THz band [30], graphene had been widely studied for THz protection [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. However, the atomic monolayer graphene is almost transparent to THz wave, so the overall intrinsic absorption of monolayer graphene is highly limited [14,15].…”
Section: Thz Shieldingmentioning
confidence: 99%
“…Landy et al reported a metamaterial absorber with perfect absorption characteristics for the first time [21]. Since then, various metamaterial absorbers operating in various frequency regions were achieved, from microwave to infrared range [22][23][24]. In terahertz region, Tao et al demonstrated the first narrowband absorber [25].…”
Section: Introductionmentioning
confidence: 99%